Improvement of corrosion resistance for brass in 3.5% NaCl media by using 4- fluorophenyl-2, 5-dithiohydrazodicarbonamide - ALFALAH, Mothana Ghazı Kadhım; ELID, Ahmed; ABDO ALİ, Amgad Ahmed; KAMBERLİ, Ersin; NAZLI, Bahar; KOYUN, Sevilay; TOSUN, Alihan; KADİRLİOĞLU, Muhammed; ELKASSUM, Fatma; SALEH, Saleh Quddus; OBIED, Abdulrahman; KANDEMİRLİ, Fatma (The Turkish Chemical Society, 2023)
Corrosion poses a significant challenge for numerous industries. The use of corrosion inhibitors is essential within these industries. The efficacy of environmentally friendly corrosion inhibitors should remain high even when used at low concentrations. In the present study, the compound 4- fluorophenyl-2,5- dithiohydrazodicarbonamide (FTSC) was used as a corrosion inhibitor for brass in 3.5% NaCl solution. The inhibitor efficiency was determined by using a series of electrochemical techniques such as open circuit potential (OCP), potential dynamic polarisation (PDP), linear polarisation resistance (LPR), and electrochemical impedance spectroscopy (EIS). All experimental tests have been done in stagnant conditions. The findings of the experiments revealed that the compound FTSC looked to be of the cathodic type. Furthermore, the maximum inhibitor efficiency was reached at 98.28% at 1 × 10-3 and at an immersion time of 1 h. The current density was reduced from 16.5 to 0.284 A.cm-2. The adsorption of compound on the brass surface in 3.5% NaCl solution obeyed the Langmuir isotherm with a low negative value of the standard Gibbs free energy of adsorption (-33.8 kJ/mol ΔGads (chemisorption and physisorption). The results confirmed that the compound FTSC can be used as a corrosion inhibitor for brass in 3.5% NaCl.
Keywords: corrosion inhibition; electrochemistry; brass; Electrochemistry; Elektrokimya